Overlooked trade‐offs of environmentally protective hydropower operation: Impacts to ancillary services and greenhouse gas emissions. (5th September 2018) - Rand, Joseph
Abstract: The relicensing of large hydropower projects in the United States often enforces environmental constraints such as minimum instream flows. These requirements can reduce hydropower's negative environmental impacts but may come at a cost of reduced electric generation and revenue. During the federal hydropower relicensing process, participants negotiate these environmental and economic trade‐offs based on coarse models, often conflating impacts on generation and revenue, overlooking ancillary services (AS) markets, and ignoring potential greenhouse gas (GHG) implications. Using a case study of a 362‐MW hydropower project in California, this research conducts higher resolution modelling to compare energy generation, AS provision, revenue, and GHG impacts of two hydropower operating regimes. The environmentally protective regime reduces average generation by 6% but increases AS provision by 2%. Total average revenue decreases by 3.5% under environmental constraints using current electricity prices (and by only 1.1% when modelled with projected 2030 electricity prices), indicating that generation impacts should not be equated with revenue impacts during relicensing. In the California electricity market, this reduced hydropower generation is replaced primarily by natural gas, resulting in an estimated 30, 000 additional tons of CO2 emitted annually. These positive and negative externalities are not adequately examined in the hydropower relicensing process.